A sensitivity study on the effect of mass distribution of a single-tether spherical point absorber. (October 2019) - Meng, Fantai; Cazzolato, Benjamin; Li, Ye; Ding, Boyin; Sergiienko, Natalia; Arjomandi, Maziar
Abstract: In previous work, a single-tether submerged spherical point absorber with asymmetric mass distribution (SPAMD) was proposed to enable harvesting wave energy induced by the surge and heave motion of the buoy. By taking advantage of the motion coupling arising from the asymmetric mass distribution of the buoy, the SPAMD was found to be up to 3 times more efficient than a generic single-tether point absorber (with uniform mass distribution buoy) under regular waves. For motion-coupled systems like the SPAMD, the mass distribution is a significant factor that governs the kinematics and the efficiency of the device. Therefore, in this paper, a 3DOF (surge, heave and pitch) spectral-domain model considering viscous drag was developed, to investigate the sensitivity of the mass distribution on the power output of the SPAMD in irregular waves. The aim of the sensitivity study is to provide a guideline for the wave energy industry when designing such devices. At the end of this paper, the yearly mean power output of the SPAMD with optimal mass distribution was assessed at three test sites near Yeu Island (France), Perth (Australia) and Sydney (Australia). It was found that in such sea sites, the SPAMD was at least 1.5 times more efficient than the generic single-tether point absorber, indicating that the SPAMD might have a significant commercial potential. Furthermore, for the three sites investigated, the performance of the SPAMD was found to be relatively tolerant to non-optimal PTO configuration, implying that sea-state specific tuning is unnecessary. Highlights: A SPAMD with low weight-to-buoyancy ratio is more productive at small wave periods. The mass ratio of the SPAMD has a limited impact on the power output. Mass-offset position has the greatest impact on the power production of the SPAMD. PTO loading is relatively insensitive to the mass-offset position. SPAMD can produce up to 53% more annual mean power than the generic single-tether PA.